A promoção do direito fundamental à saúde a partir da tributação extrafiscal :uma análise em face do consumo de tabaco, bebida alcóolica e de alimentos não saudáveis - Bernaud, Renata Rolla (2015)
The health promotion idea is closely linked to the right to a dignified and healthy life. As a fundamental right guaranteed to all, health in its preventive form, granting the State the duty to protect the population. Noncommunicable diseases, such as cancer, diabetes, cardiovascular and respiratory diseases, just surpass the number of people affected by communicable diseases. The concern is global and measures need to be taken to contain this catastrophe. Responsible for the main risk factors for noncommunicable diseases, tobacco, alcohol and unhealthy fods are key player in this scenario. Curb consumption of these produtcs has become a necessity of the contemporary world. In this sense, the focus of research is the study of interventional measure of prices and incident taxes on tobacco, alcohol and unhealthy foods. It is know that taxation, in addition to its mais tax collection function can be used to encourage or discourage behavior. Thus, through the extrafiscality and specifically, taxes on consumption, we intend to see reduced the consuption of products considered unhealthy, so that is guaranteed to all the health promotion.